Squeezing Bulk Plasmon Polaritons through Hyperbolic Metamaterials for Large Area Deep Subwavelength Interference Lithography. Issue 9 (20th April 2015) - Liang, Gaofeng; Wang, Changtao; Zhao, Zeyu; Wang, Yanqin; Yao, Na; Gao, Ping; Luo, Yunfei; Gao, Guohan; Zhao, Qing; Luo, Xiangang
<x xml:space="preserve">Abstract</x> Hyperbolic metamaterial composed of SiO2/Al films are explored to squeeze out bulk plasmon polaritons (BPPs) to produce large area and uniform deep subwavelength interference patterns. As examples, two and four BPPs interference lithography with half pitch 45 nm (≈λ/8) are demonstrated in experiments. Much deeper resolution up to 22.5 nm (≈λ/16) and variety of BPPs interference patterns are feasible. The period of grating structures for transferring photons to BPPs is much larger than that of BPPs interference patterns, facilitating the structures fabrication by simple and low cost methods like large area laser interference lithography. It is believed that the method provides a cost‐effective, parallel, and large area nanofabrication way.